1954
DOI: 10.1121/1.1907397
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Earphones in Ears and Couplers

Abstract: Applied voltage responses of seven earphones on both ears of fourteen people were obtained with the aid of a probe tube microphone inserted into the volume enclosed by the earphone. Treatment of the response data by the method of analysis of variance allowed separation of variance effects due to error in repeated measurement, dissimilarity between a given person's ears, and differences among individuals. The latter are found to be the most important effects to contend with in audiometric practice. Effects of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1963
1963
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…5,6,13,14,17,18 In all of these studies, it has been shown that these functions are different, especially at low ͑for some earphones͒ and high frequencies ͑for almost all earphones͒. Usually, the level reduction caused by leakage seen in the functions measured in human ears for the supra-aural earphones does not exist in the transfer functions measured in the coupler, which is confirmed in the present investigation.…”
Section: B Variations In Earphone Transfer Functionssupporting
confidence: 87%
See 2 more Smart Citations
“…5,6,13,14,17,18 In all of these studies, it has been shown that these functions are different, especially at low ͑for some earphones͒ and high frequencies ͑for almost all earphones͒. Usually, the level reduction caused by leakage seen in the functions measured in human ears for the supra-aural earphones does not exist in the transfer functions measured in the coupler, which is confirmed in the present investigation.…”
Section: B Variations In Earphone Transfer Functionssupporting
confidence: 87%
“…10,11 The procedure for determining the acoustical output of earphones based on usage of either rigid couplers or so-called artificial ears has passed through different stages of development and standardization. Unfortunately, the results from previous investigations 5,6,[12][13][14][15][16] have indicated that none of the couplers or artificial ears give completely satisfactory results for accurate calibration of audiometric earphones. Important differences between the pressures generated in the subject ear canal and the coupler reported for different combinations of the earphones and the couplers 5,6,14,[17][18][19] have shown that calibrating couplers have not duplicated the acoustical load of a human ear as precisely as desired for audiometric tests.…”
Section: A Background and Previous Investigationsmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, the stimuli in the experiment were presented to the listeners via Permoflux (Chicago, IL) PDR-8 headphones (Lehiste and Peterson, 1959). The frequency response of this particular brand of headphone is reported to be flat from 0.2 to 4 kHz, with a 20 dB drop in response at 8 kHz (e.g., Burkhard and Corliss, 1954). Because of the roll-off in the high-frequency response of the headphones used in the experiment, it is likely that the vowel stimuli contained significantly reduced levels of high-frequency acoustic information (i.e., frequency information above 4 kHz), irrespective of the tape speed used for recording and playback.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of the earphone output for the calibrated electrical signal by a microphone coupled to an artificial ear then furnished reference equivalent threshold sound pressure levels (RETSPLs) for the earphone by which other earphones of the same type could then be calibrated using an artificial ear. An artificial ear is a device that couples an earphone to a microphone through a physical volume intended to match the volume enclosed by the earphone on a human ear (Burkhard & Corliss, 1954). Calibration of other types of earphone required a loudnessbalancing procedure in which a group of subjects compared the loudness of the calibrated earphone to other earphone types, the electrical voltages that must be applied to the earphone under consideration that correspond to reference normal thresholds constituting the calibration for that earphone (Beranek, 1993).…”
mentioning
confidence: 99%